2004
DOI: 10.1586/14779072.2.4.503
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol: improving walking distance in patients with intermittent claudication

Abstract: Intermittent claudication is a common, disabling symptom of peripheral arterial disease that limits walking distance and is associated with an increased cardiovascular risk of acute limb- or life-threatening complications. Very few patients with intermittent claudication (<7%) are suitable candidates for surgical revascularization, yet in contrast to the treatment of stable angina, few effective medical therapies (apart from exercise) are available for the symptomatic relief of intermittent claudication. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It has a therapeutic focus on the inhibition of phosphodiesterase activity and suppression of cAMP degradation, resulting in increased cAMP in platelets and blood vessels and leading to inhibition of platelet aggregation and vasodilation [34]. Cilostazol is indicated for the treatment of intermittent claudication in patients with PAOD [35,36]. In recent years, cilostazol has been used for the secondary prevention of brain infarction through its antiplatelet antithrombotic effects [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a therapeutic focus on the inhibition of phosphodiesterase activity and suppression of cAMP degradation, resulting in increased cAMP in platelets and blood vessels and leading to inhibition of platelet aggregation and vasodilation [34]. Cilostazol is indicated for the treatment of intermittent claudication in patients with PAOD [35,36]. In recent years, cilostazol has been used for the secondary prevention of brain infarction through its antiplatelet antithrombotic effects [37].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, cilostazol has been used for the secondary prevention of brain infarction through its antiplatelet antithrombotic effects [ 37 ]. Furthermore, some studies have shown that cilostazol can prevent the proliferation of smooth muscle cells, consequently increasing peripheral blood flow and insulin sensitivity by reducing inflammation [ 35 , 38 ]. However, insufficient data are available to explain whether cilostazol increases the functional status of the involved lower extremities, improves primary patency in patients with CLI, as well as subsequent improvement in quality of life, and reduces the occurrence of adverse cardiovascular events and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Cilostazol has shown improved cardiac safety in comparison to milrinone. In a meta-analysis of eight randomized, double-blind, placebo-controlled clinical trials, cilostazol increased pain-free walking by 67% and was better than pentoxifylline, the only other drug approved for PAD that works by different mechanisms [424].…”
Section: Cilostazolmentioning
confidence: 99%